Art of Documentary Editing - Muhammad Haazim, Khalik; Nurul Rahayu, Norianto; Chong Lee, Yow (Mini Film Festival, 2022)
Infographics on Art of Editing Documentary. The content is extracted from MFF Doc Workshop (4) presented by Ms. Phạm Thu Hằng, designed by Haazim, Rahayu, advised and edited by Yow.